PENGARUH BRAND AWARENESS, PERCEIVED QUALITY, BRAND ASSOCIATION, dan BRAND LOYALTY TERHADAP BRAND ATTITUDE MELALUI EFEKTIFITAS IKLAN SHAMPO L’OREAL DI SURABAYA - HERTANTO, YOHANES CHRISTIAN (Universitas Katolik Widya Mandala Surabaya, 2013)
For instance, if a brand is introduced or communicated through advertising in various media, this will cause brand awareness as a first step to a better known brand audience and be an alternative product options. Companies that actively cultivating brand association in the minds of certain consumer can form a different image with other brands. Finally, if a firm is always striving to make their target consumers are satisfied with the quality of its products, the consumer will have a loyalty to the brand that would later cause consumers purchase the product again in the future. The research aims to know the influence of brand awareness, perceived quality, brand association, and brand loyalty towards the brand attitude L'oreal in Surabaya with advertisement effectiveness as intervening variable. In this study used is the conclusive research on the study of experimental or causal research. Sampling-taking techniques used are non probability sampling. The type of method used is the purposive sampling. The sample used was 200 consumers L'oreal in Surabaya. Data were collected using a questionnaire. The technique used is the analysis of structural equation modeling with Lisrel program assistance. The results of this analysis indicate that brand awareness, perceived quality, brand association, and brand loyalty effect directly against the effectiveness of the ads. In addition, the study found that the effectiveness of advertising influence on brand attitude.